Study Of Abnormal Lipids And Apolipoprotein-B Composition In Diabetic And Nondiabetic Chronic Renal Failure Patients - DR. MEERA SHIVASHEKAR; MR. ASHOK VARDHAN NANDIGAM; DR. EBENEZER WILLIAM; DR.PADMANABHAN (International Journal of Pharma and Bio Sciences, 2012)
The study was aimed to investigate the role of lipids and Apo-B lipoprotein composition in diabetic and non diabetic CRF patients. The study included 50 diabetic and 50 non diabetic renal failure patients receiving regular Hemodialysis, between the age group of 35 ± 20 years and 50 age and sex matched healthy controls. Heparinized blood samples were collected before Hemodialysis, and analyzed for Apo-B containing lipoproteins by immunoturbidimetric method. Serum Total cholesterol, Triglycerides, LDL and HDL were analyzed by using commercially available kits in Olympus auto analyzer. Apo lipoprotein-B, LDL cholesterol, total cholesterol and triglyceride levels were significantly elevated in Diabetic CRF patients. But HDL levels were characteristically reduced in all patients. Apo-B, LDL levels showed a significant decrease in non diabetic renal failure patients compared with diabetic CRF patients. CRF patients on Hemodialysis showed compositional and metabolic abnormalities of plasma lipoproteins. The study is aimed to investigate the abnormalities in the lipids and apolipoprotein-B concentration in diabetic and non diabetic CRF patients.